effect of Aqueous extract of tobacco leaves on blood hemoglobin, mean corpuscular hemoglobin (MCH) and on mean corpuscular hemoglobin concentration (MCHC) in the red blood cells of Syrian Hamsters. (Latakia University Journal -Biological Sciences Series, 2018)
This   study was performed to investigate the effect of aqueouse extract of tobacco leaves on blood parameters 15 Males Hamster were used in this study , they were divided into three groups : control , and two experimental groups ( five hamster in each  ) , the control group was given distilled water , while the experimental groups were received oral doses of aqueouse extract of tobacco leaves 5.8 mg / kg of body weight and 11.8 mg / kg of body weight  daily for (24)day . The Results showed a significant decrease (P